Information systems security management - Nyamongo, Doreen Moraa (Strathmore University, 2012)
Institutions of higher learning have a desire to supply knowledge to all those who seek It. Currently Universities are finding that they have to balance between their initial Goals and adoption of adequate measure to protect sensitive information about Student, alumni, workers and their business partners. Applying Information security to University IT systems is strategically important to maintaining overall business Continuity and competitive edge. Given the fad that a university environment poses Unique challenges related to diverse roles and the tendency of people viewing things Differently, it is challenging to successfully implement information systems security In such a setting. The diversification of views in/the university environment has led to Increased demands from the users of the systems hence continuous review and Improvements of this systems quality is required, It is necessary to have a high level Of information systems security management in institutions of higher learning in Kenya. : This research undertook both quantitative and qualitative approaches of information Security management in institutions of higher learning with the use of both primaries And secondary data sources. A descriptive research design was employed with the use Of questionnaires as principal data collection instrument. The questionnaire was Distributed to all the individuals in the sample. The research was carried out at all Private chartered universities in Kenya. The sample size was drawn from the lCT directors and lCT staff of these universities. Collected data was analyzed using both Quantitative and qualitative data analysis approaches, Data from the questionnaires Was checked for completeness, coded and logged into the computer system using Statistical Package for Social Science (SPSS). I In The study found out those institutions of higher/learning in Kenya is ready to adopt And improve on their information systems security management by regularly updating Management on security updates (64.5%) but ~hen having dedicated office dealing With security issues (58.1 %) and a security practitioner being part of top management (54.8%) will ensure that updates on security issues to top management are followed up And worked on, staff training on ISSM (22.6 %[), Joint, involved and support of other Departments (52.0%) will go a long way in improving the university's 18SM. However viruses (58.1%), user errors (4~.4%), theft of computers (45.2%), Compromising the system (45.1%) and system or software errors (38.7%) among Others continue to be the major challenges affecting 18SM in institutions of higher Learning. in The study concludes that institutions of higher learning should rethink their ways of Handling security of their most valued assets. Hence there is a need to highlight an effective strategy that will help institutions of higher learning to achieve effective information security management. .
A case of private chartered universities in Kenya
Submitted in partial fulfillment of the requirements for the Degree of Master of Science in Information Technology at Strathmore University
Keywords: Information Systems Security Management; Private Chatered Universities; Kenya